A short course in soil-structure engineering of deep foundations, excavations and tunnels - Ng, C. W. W. (Thomas Telford, 2004)
This text is divided into three parts - effectively three short courses - focusing on the following three major geotechnical challenges of static soil-structure interaction problems: deep foundations; multi-propped deep excavations; and bored and open face tunnels beneath cities.